2016
DOI: 10.7589/2015-08-219
|View full text |Cite
|
Sign up to set email alerts
|

Avian Malaria (Plasmodium spp.) in Captive Magellanic Penguins (Spheniscus magellanicus) from Northern Argentina, 2010

Abstract: We report two cases of lethal avian malaria in Magellanic Penguins (Spheniscus magellanicus) captive at San Clemente del Tuyú, Argentina, approximately 560 km north of Argentinean breeding colonies of Magellanic Penguins. Blood smears revealed both penguins were concurrently infected by Plasmodium (Haemamoeba) tejerai, Plasmodium (Huffia) sp., and Plasmodium (Novyella) sp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…infections in Valdivia, Chile (39°49′S) (Carvajal and Alvarado, 2009), and San Clemente del Tuyú, Argentina (36°20′S) (Vanstreels et al . 2016 b ), whereas all studies have failed to detect blood parasites in wild Magellanic penguins sampled south of 40°S (Fig. 1).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…infections in Valdivia, Chile (39°49′S) (Carvajal and Alvarado, 2009), and San Clemente del Tuyú, Argentina (36°20′S) (Vanstreels et al . 2016 b ), whereas all studies have failed to detect blood parasites in wild Magellanic penguins sampled south of 40°S (Fig. 1).…”
Section: Discussionmentioning
confidence: 97%
“…Geographic distribution of studies investigating the occurrence of blood parasites in Magellanic penguins in relation to the species' natural distribution and historical precipitation data. (Vanstreels et al 2016b), whereas all studies have failed to detect blood parasites in wild Magellanic penguins sampled south of 40°S (Fig. 1).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…schizonts and mixed inflammatory infiltrates in mainly liver and spleen, avian malaria was diagnosed (Tm 1–3, 5) [3,4]. However, when birds had myocardial degeneration (Tm 4) or encephalitis (Tm 7–8, Sn 4), tissues were submitted for USUV RT-PCR.…”
Section: Outbreak In Birdsmentioning
confidence: 99%
“…The birds revealed a massive infestation of exoerythrocytic meronts of Plasmodium parasites in various organs including the brain, spleen and lungs. The majority of cited studies or case reports have shown that avian haemosporidian parasites can be dangerous not only for non-adapted bird species like, for example, penguins [ 24 ] or endemic Hawaiian honeycreepers of the Drepaniidae [ 9 ] that did not co-evolve with these parasites, but also in bird species, which have been evolutionarily exposed to these infections for long periods, for example, the blackbird Turdus merula in Europe [ 15 ]. Based on limited available experimental data and scarce case reports from wildlife, it is difficult to estimate how many individuals from certain populations get malaria infections, how many of them survive, and what are the behavioural changes in the parasitized birds.…”
Section: Introductionmentioning
confidence: 99%